2017
DOI: 10.1021/acs.jchemed.6b00451
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Evaluation of Three Types of Student-Generated Videos as Instructional Support in Organic Chemistry Laboratories

Abstract: This study was designed to evaluate the effectiveness of student-generated videos as a supplement to teaching assistant (TA) instruction in an undergraduate organic chemistry laboratory. Three videos covering different aspects of lab instruction (experimental technique, use of instrumentation, and calculations) were produced using student-generated scripts. A laboratory classroom was outfitted with video cameras and sound recording equipment that allowed the research team to monitor all TA−student and student−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 16 publications
4
62
0
1
Order By: Relevance
“…Findings indicated that the video and interactive computer-assisted activities increased the amount of time students spent completing the pre-lab activities and decreased the number of errors and total time spent on the experiment. This increased efficiency in the laboratory has also been seen in other studies 34,172 . Pre-laboratory instructional videos can also decrease the number of questions students ask about procedural issues, while increasing the number of questions related to calculations or theory 31,38,[172][173] .…”
Section: Pre-laboratory Videossupporting
confidence: 82%
See 4 more Smart Citations
“…Findings indicated that the video and interactive computer-assisted activities increased the amount of time students spent completing the pre-lab activities and decreased the number of errors and total time spent on the experiment. This increased efficiency in the laboratory has also been seen in other studies 34,172 . Pre-laboratory instructional videos can also decrease the number of questions students ask about procedural issues, while increasing the number of questions related to calculations or theory 31,38,[172][173] .…”
Section: Pre-laboratory Videossupporting
confidence: 82%
“…This increased efficiency in the laboratory has also been seen in other studies 34,172 . Pre-laboratory instructional videos can also decrease the number of questions students ask about procedural issues, while increasing the number of questions related to calculations or theory 31,38,[172][173] . This change has been explained as a result of having the videos remove some of the cognitive load of performing the experiments and shifting the focus to thinking about the calculations and chemistry behind the experiments 32,172 .…”
Section: Pre-laboratory Videossupporting
confidence: 82%
See 3 more Smart Citations